THE MOTIF OF MYSTERY IN THE DETECTIVE STORY TRUCTURE IN ANATOL KURDYDYK’S «THREE KINGS AND A LADY» - Мафтин, Н. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyses the peculiarity of the implementation of the intertextual motif of mystery in the detective story structure. It has been proved that the plot saturation by the inner textual motifs which are paralleled and opposed to the mystery motif and promote the usage of a small form strategy in the story contexture. Changing of central motif modifications into the motifs of a gambling game, love and faithlessness, a woman-angel and a horsewoman moves the plot, stimulates the dynamics and the tensity of the development of the events.